(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
The objectives of this study were to analyze the cases that underwent relaparotomy and identify indications of primary and relaparotomy surgeries, relaparotomy findings, and procedures undertaken and find out avoidable risk factors of such emergency situations. This was a retrospective descriptive study done in Dhaka National Medical College Hospital during the period from July 2011 to June 2013. Out of 6983 operations (Obstetric and Gynae) 13 cases needed relaparotomy. In ten case primary operations were performed in this hospital and three were performed in outside clinics( one outside Dhaka).Indications of relaparotomy were, internal haemorrhage, foreign body, rectus sheath haematoma, secondary PPH, fecal fistula, post surgery adhesion. Procedure performed during repeat operations were hysterectomy, resuturing of uterine incision ,peritoneal toileting and removal of blood clot, removal of foreign body, drainage of rectus sheath haematoma, fecal fistula repair, adhesiolysis. To reduce the risk of relaparotomy and to minimize the sufferings of the patients from relaparotomy, proper case selection during primary operation, competency of the surgical team, appropriate surgical procedures, prompt identification of complication and early necessary intervention should be maintained in every hospital. J. Dhaka National Med. Coll. Hos. 2014;20(01):47-49